Structural Insights On Brugia Malayi Transglutaminase With Cinnamoyl Derivatives - A Molecular Docking Approach - SRIKUMAR P S; ROHINI K (International Journal of Pharma and Bio Sciences, 2012)
The parasite Brugia malayi, one of the causative agents for human lymphatic filariasis, found endemic in tropical and sub tropical countries like India, Indonesia, Malaysia and Thailand. The enzyme transglutaminase (TGase) is involved in the growth and development stages of parasite. Transglutaminase has been found to be a better target for the anti filarial agents due to its critical role in the parasite’s growth and development. In our study, we reported cinnamoyl derivatives as potent inhibitors for Brugia malayi transglutaminase. The computational molecular docking approach was used to confirm the inhibition of cinnamoyl derivatives with the enzyme transglutaminase to block the growth and development of parasite Brugia malayi and acts as a novel anti filarial agent.